Hepatic histology and cage production of Nile tilapia hormonally masculinized or nonmasculininized - Gayão, Ana Laura Borba de Andrade; Buzollo, Hellen; Fávero, Gisele Cristina; Silva Junior, Ancilon Araújo e; Portella, Maria Célia; Cruz, Claudinei da; Carneiro, Dalton José (Pesquisa Agropecuaria Brasileira, 2013)
The aim of this work was to evaluate the performance and the liver structure health of Nile tilapia hormonally masculinized or nonmasculinized, reared in cages with two protein levels. Two groups of Nile tilapia of Thai lineage (total 2,400), with 127 g initial average weight, were distributed in a completely randomized design with four treatments, in a 2x2 factorial arrangement, corresponding to the groups of hormonally masculinized or nonmasculinized fish, and to diet protein level of 28 or 32% of crude protein, with three replicates. After 115 days feeding, there was no interaction between the factors for final weight, weight gain, feed conversion rate, final length and survival. There was no difference between hormonally masculinized and nonmasculinized fish for final weight, weight gain, and survival, which shows the possibility of their production in cages, without the need of hormonal masculinization. Crude protein at 32% in the diet enables a better performance for both groups. Histological changes in the liver – such as increased cell volume, disruption of the cord‑like arrangements, and increase of vesicles in the hepatocytes – are found in hormonally masculinized fish, and are more pronounced in fish fed 32% crude protein in the diet.